2004
DOI: 10.1023/b:jmte.0000021879.74957.63
|View full text |Cite
|
Sign up to set email alerts
|

Initiating Change in Prospective Elementary School Teachers' Orientations to Mathematics Teaching by Building on Beliefs

Abstract: ABSTRACT. Many mathematics educators have found that prospective elementary school teachers' beliefs interfere with their learning of mathematics. Often teacher educators consider these beliefs to be wrong or naïve and seek to challenge them so prospective teachers will reject them for more generative beliefs. Because of the resilience of prospective teachers' beliefs in response to these challenges, teacher educators could consider alternative ways of thinking about and addressing beliefs, particularly the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 26 publications
(23 reference statements)
4
85
0
5
Order By: Relevance
“…Noting various concerns, such as the lack of sound subject matter knowledge and the strong influence of prospective teachers' past experiences as students, the consensus in the mathematics education community is that it is essential to provide prospective teachers with ample opportunities to improve and transform their knowledge, beliefs, and actual teaching practice.However, what prospective teachers bring to teacher education programs is, admittedly, often difficult to greatly change in the limited time period.For example, candidates' beliefs about what to teach and how to teach it have been consciously or unconsciously developed through many years of observations of their own K-12 teaching practices, and it is almost improbable to completely transform their beliefs (e.g., Ambrose, 2004;Doerr&Lesh, 2003;Eisenhart, Borko, Underhill, Brown, Jones, &Agard, 1993;Thompson, 1992).…”
Section: Supporting Prospective Teachers: Problems and Possibilitiesmentioning
confidence: 99%
“…Noting various concerns, such as the lack of sound subject matter knowledge and the strong influence of prospective teachers' past experiences as students, the consensus in the mathematics education community is that it is essential to provide prospective teachers with ample opportunities to improve and transform their knowledge, beliefs, and actual teaching practice.However, what prospective teachers bring to teacher education programs is, admittedly, often difficult to greatly change in the limited time period.For example, candidates' beliefs about what to teach and how to teach it have been consciously or unconsciously developed through many years of observations of their own K-12 teaching practices, and it is almost improbable to completely transform their beliefs (e.g., Ambrose, 2004;Doerr&Lesh, 2003;Eisenhart, Borko, Underhill, Brown, Jones, &Agard, 1993;Thompson, 1992).…”
Section: Supporting Prospective Teachers: Problems and Possibilitiesmentioning
confidence: 99%
“…Past experiences can have a very negative impact on a person's disposition towards learning mathematics (Ambrose, 2004;Biddulph, 1999, Cornell, 1999Tooke & Lindstrom, 1998). Such feelings can affect the learning and teaching of mathematics and need to be addressed (Biddulph, 1999;Grootenboer, 2003;Hawera, 2004;Schuck & Grootenboer, 2004).…”
Section: Why Use Mathematics Investigations?mentioning
confidence: 99%
“…Additionally, numerous other researchers, including Ambrose (2004) asserted that mathematical knowledge and beliefs related to this knowledge, as well as the teaching of math, are strongly entwined. Meanwhile, Poulson, Avramidis, Fox, Medwell, & Wray (2001) indicated that a complex connection exists between a teacher's beliefs and his or her teaching practices; beliefs drive performance, while teaching experience and practices have the ability to change (or supplement) an individual's beliefs.…”
Section: Introduce the Problemmentioning
confidence: 99%